Heritage Education and Virtual Archaeology Applications in Museums and Archaeological Sites: A case study for the Santa Pola Sea Museum (Spain) - Cerdá Bertoméu, María José; Mateo Corredor, Daniel; Álvarez Tortosa, Juan Francisco (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The main objective of this research is to reflect on the effectiveness of virtual archaeology applications in school audiences for the understanding and learning of archaeological heritage. This is intended to appreciate how technologies such as Augmented Reality and Virtual Reality can add value to the educational proposals made by museums and archaeological sites that do not have this inclusion. The exploratory analysis of the case is carried out at the Santa Pola Sea Museum (Spain), which has developed this type of applications in the Roman archaeological site it manages, the Portus Ilicitanus.